Effect of Incremental Endoscopic Maxillectomy on Surgical Exposure of the Pterygopalatine and Infratemporal Fossae - Upadhyay, Smita; Dolci, Ricardo L. L.; Buohliqah, Lamia; Fiore, Mariano E.; Filho, Leo F.S. Ditzel; Prevedello, Daniel M.; Otto, Bradley A.; Carrau, Ricardo L. (Journal of Neurological Surgery Part B: Skull Base, 2016)
Objective Access to the pterygopalatine and infratemporal fossae presents a significant surgical challenge, owing to their deep-seated location and complex neurovascular anatomy. This study elucidates the benefits of incremental medial maxillectomies to access this region. We compared access to the medial aspect of the infratemporal fossa provided by medial maxillectomy, anteriorly extended medial maxillectomy, endoscopic Denker approach (i.e., Sturmann-Canfield approach), contralateral transseptal approach, and the sublabial anterior maxillotomy (SAM).Methods We studied 10 cadaveric specimens (20 sides) dissecting the pterygopalatine and infratemporal fossae bilaterally. Radius of access was calculated using a navigation probe aligned with the endoscopic line of sight. Area of exposure was calculated as the area removed from the posterior wall of maxillary sinus. Surgical freedom was calculated by computing the working area at the proximal end of the instrument with the distal end fixed at a target.Results The endoscopic Denker approach offered a superior area of exposure (8.46 ± 1.56 cm2) and superior surgical freedom. Degree of lateral access with the SAM approach was similar to that of the Denker.Conclusion Our study suggests that an anterior extension of the medial maxillectomy or a cross-court approach increases both the area of exposure and surgical freedom. Further increases can be seen upon progression to a Denker approach.
Keywords: infratemporal fossa; endoscopic; medial maxillectomy; transseptal; endoscopic Denker; surgical freedom